Multimodal emotion recognition from Speech and text using heterogeneous ensemble techniques - Rafidul Islam, Sheikh Md; Gomes, Maria; Hossain, Mehran; Raihana, Ramisha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.